Posicionamiento en entornos digitales: el caso de Netflix y su interacción con los públicos - Dra. María Jesús FERNÁNDEZ TORRES,Dr. Eduardo VILLENA ALARCÓN, (Fonseca, Journal of Communication, 2023)
The Internet and the consumption of audiovisual content are two inseparable terms. It is a fact that the emergence of new technologies has changed the way in which audiovisual content is sought worldwide. Citizens more frequently view content online, which has favoured the emergence of new business models to meet these needs.